Influencia de la fuerza de agarre y la aparición de trastornos musculoesqueléticos en conductores profesionales en Ibarra y Chone, 2024 - Molina Ormaza, Gema Nathaly (2025)
Musculoskeletal disorders represent a significant problem in the workplace, affecting the health and productivity of workers, potentially leading to permanent disabilities. They are common in occupations involving repetitive activities or prolonged postures. The aim of the study was to determine the influence of grip strength on the onset of musculoskeletal disorder symptoms in professional drivers. A cross-sectional, quantitative, descriptive, correlational, non-experimental study was conducted, the sample consisted of 277 professional drivers. Grip strength was measured using a CAMRY hand dynamometer, and the Cornell Musculoskeletal Discomfort Questionnaire (CMDQ) was administered. Drivers exhibited adequate grip strength, with a slight dominance in the right hand (42.1 kg vs. 41.6 kg), 22% (n=61) of the drivers were at moderate or high risk of musculoskeletal disorders in the neck, 17% (n=46) in the shoulders, and 25% (n=68) in the lower back. In conclusion, no statistically significant association was found between grip strength and the occurrence of MSDs; grip strength alone is not a determining factor in the development of these disorders in the studied population.